The ASC Speck and NLRP3 Inflammasome Function Are Spatially and Temporally Distinct - Nagar, Abhinit; Rahman, Tabassum; Harton, Jonathan A. (Frontiers in Immunology, 2021)
Although considered the ternary inflammasome structure, whether the singular, perinuclear NLRP3:ASC speck is synonymous with the NLRP3 inflammasome is unclear. Herein we report that the NLRP3:ASC speck is not required for nigericin-induced inflammasome activation, but facilitates and maximizes IL-1β processing. Further, the NLRP3 agonists H2O2 and MSU elicited IL-1β maturation without inducing specks. Notably, caspase-1 activity is spatially distinct from the speck, occurring at multiple cytoplasmic sites. Additionally, caspase-1 activity negatively regulates speck frequency and speck size while speck numbers and IL-1β processing are negatively correlated, cyclical, and can be uncoupled by NLRP3 mutations or inhibiting microtubule polymerization. Finally, when specks are present, caspase-1 is likely activated after leaving the speck structure. Thus, the speck is not the NLRP3 inflammasome itself, but is instead a dynamic structure which may amplify the NLRP3 response to weak stimuli by facilitating the formation and release of small NLRP3:ASC complexes which in turn activate caspase-1.